2015
DOI: 10.1016/j.otsr.2015.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Meniscoplasty for lateral discoid meniscus tears: Long-term results of 14 cases

Abstract: IV (retrospective study).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 18 publications
1
33
0
1
Order By: Relevance
“…Management of torn discoid meniscus has evolved to more conservative surgery. Partial meniscectomy using the saucerization technique resecting the central portion of the meniscus in order to recreate the shape of a normal meniscus has obtained better results in medial and long-term follow-up for torn discoid meniscus than total meniscectomy [ 12 , 16 ]. Currently, tears in medial discoid menisci are treated with saucerization and suture when the type of lesion allows so [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Management of torn discoid meniscus has evolved to more conservative surgery. Partial meniscectomy using the saucerization technique resecting the central portion of the meniscus in order to recreate the shape of a normal meniscus has obtained better results in medial and long-term follow-up for torn discoid meniscus than total meniscectomy [ 12 , 16 ]. Currently, tears in medial discoid menisci are treated with saucerization and suture when the type of lesion allows so [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found no difference between meniscoplasty and total meniscectomy as to shortterm clinical outcomes [36][37][38], but the clinical efficacy of meniscoplasty is better than that of total meniscectomy in the long-term follow-up [3,24,[38][39][40][41][42]. Other studies have shown that the long-term outcomes of meniscoplasty with or without repair are satisfactory, without statistical difference [9,38,39,41,43,44]. Moreover, Perkins et al [45] founded that, for meniscocapsular tears, meniscoplasty with repair is related to low rates of revision surgery and good intermediate-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have reported good long-term clinical results, radiographically, many studies showed a high rate of early degenerative changes of the lateral compartment of the knee [16, 17]. Therefore, a recently recommended treatment plan for a symptomatic DLM tear is arthroscopic meniscal reshaping using partial meniscectomy, with or without meniscal repair [18, 19]. None of the patients in our study with inverted-type DLM tears had a posterior peripheral rim tear or instability of the posterior horn, but the inverted portion of the central discoid body was torn.…”
Section: Discussionmentioning
confidence: 99%